Handling Slum Areas in Tanjung Tiram and Medang Deras Districts in Batubara Regency - Irwansyah Siagian; Abdi Sugiarto; Cut Nuraini (CV. Doki Course and Training, 2026)
The issue of slum housing and slum settlements remains a major challenge in regional development, particularly in coastal areas and regions experiencing relatively high population growth. Batubara Regency, as a coastal area in North Sumatra Province, faces dynamic settlement development that has not been fully balanced by the adequate provision of infrastructure, facilities, and public utilities. This study aims to analyze the existing conditions of slum housing and slum settlements in Tanjung Tiram and Medang Deras Districts, assess the conformity of slum area location designation with the provisions of Article 106 paragraph (3) of Government Regulation Number 14 of 2016 and Article 36 paragraph (7) of the Regulation of the Minister of Public Works and Housing Number 14/PRT/M/2018, and formulate integrated and sustainable priorities and strategies for slum area management. The research method employed is a qualitative approach, with data collected through document studies, field observations, and interviews with relevant stakeholders. The results indicate that slum areas in Tanjung Tiram and Medang Deras Districts exhibit varying levels of slum severity, ranging from mild to moderate and severe, influenced by limited basic infrastructure, population density, the socio-economic conditions of the community, and weak control over land use. The designation of slum area locations by the local government has normatively complied with prevailing laws and regulations and serves as an important basis for determining appropriate management patterns